Measles epidemiology and vaccination coverage in Oromia Region, Ethiopia: Evidence from surveillance, 2011–2018. Issue 31 (13th July 2021) - Yitbarek, Kiddus; Tilahun, Tizta; Debela, Tessema; Abdena, Dereje; Girma, Tsinuel
Highlights: Measles outbreak happens frequently in Oromia Region. There is a discordance between observed measles outbreak and measles vaccination coverage reports. There was a considerable difference in measles vaccination coverage between administrative report and the estimated coverage. The low actual measles coverage may explain the discordance between the observed measles outbreaks and the reported high vaccination coverage. Abstract: Despite a reported high coverage of measles-containing vaccine (MCV), low-income countries including, Ethiopia, have sustained high measles transmission with frequent outbreaks. We investigated the distribution of measles infection and vaccination in Oromia Regional State, Ethiopia. According to the World Health Organization (WHO) and the Ethiopian measles case classification guidelines, measles cases were classified as laboratory-confirmed, clinically compatible, and epidemiologically linked. We derived measles vaccination coverage estimates using reported measles vaccine efficacy and, the proportion of measles cases vaccinated with measles vaccine at least once from the surveillance data. We calculated measles effective reproduction number (Re ) in the region. Almost twenty-five thousand measles cases were reported through the surveillance system, with more than 50% of the suspected and confirmed measles cases reported in 2015. Measles had sustained and high transmission rate with uneven distribution among the zones. Children between 1 and 4 years of age and MCV unvaccinated individuals were the most affected groups. In all the zones, the average surveillance-estimated MCV coverage among both infants and under-five children was significantly lower than the WHO recommended minimum 90% threshold herd-immunity. With this level of vaccination coverage, an infected case can transmit to more than four individuals. Nevertheless, the administrative coverage reports for the concurrent period were consistently above 90%. The estimated MCV coverage across the Oromia region was well below the recommended herd-immunity threshold. It partly explains the apparent mismatch of sustained measles transmission and outbreaks despite the very high administrative coverage estimates. Oromia regional health bureau, in collaboration with key stakeholders, should make a concerted effort to increase the effective-coverage of MCV to at least 90%. Additionally, multiple-dose MCV has to be scaled-up and accompanied with appropriate geographic and age targeting using evidence from surveillance data. Immediate programmatic action is needed to improve the quality of measles surveillance.